Meningkatkan Pemahaman Pemuda GPKB Janji Angkola Tentang Karya Keselamatan Allah Dalam Yesus Kristus - Adi Suhenra Sigiro; Gebriel Lumban Tobing; Paramita Rosadi Hutagalung; Rahul Sihombing; Rinaldi J.K Lumban Toruan; Roselita Sinaga; Michael Juan Nababan (Jurnal DIKMAS, 2024)
This seminar aims to increase the understanding of GPKB Janji Angkola youth about God's work of salvation in Jesus Christ through lecture and discussion methods delivered by two presenters. Seminar material covers the concept of sin, God's salvation, and evidence of the work of salvation for humans, as well as providing opportunities for participants to ask questions and discuss. With high enthusiasm, GPKB young people attended this seminar and felt a valuable experience that left a positive impression, and it is hoped that they can make a positive contribution to society and develop the competence of students involved in this activity. The results of this activity show that understanding God's work of salvation can strengthen faith and motivate GPKB youth to play an active role in society and develop themselves spiritually.